The enforcement of cross-border competition law claims in Asia-pacific and choice of forum agreements: private litigation or arbitration?. (22nd January 2022) - Nishioka, Kazuaki
Abstract: A private plaintiff may bring an action against a defendant for the infringement of competition law. In Western countries, it is widely accepted that parties can subject to choice of forum agreements claims seeking private law remedies based on competition law infringements. Accordingly, parties are free to refer those claims to a foreign court or arbitral tribunal for their determination. In contrast, it remains an open question in most Asia-Pacific jurisdictions whether competition-related claims are subject to choice of forum agreements (in particular, an arbitration agreement). If the answer is affirmative, a number of incidental questions will arise. For instance, in what kinds of competition-related claims and under what circumstances will choice of forum agreements be applicable? With focus on international arbitration, this article will look into recent developments around the globe and then propose how states in the Asia-Pacific region should approach those issues.